THE EPISTEMOLOGICAL PRACTICES OF COMPARATIVE THEOLOGIANS - Kallungal, Martin Sebastian (Asian Horizons, 2012)
In this article, I will mainly expose and assess comparative theological views on comparison as an epistemological norm. More specifically, in what follows, taking cues from a comparative educationist, George Z.F. Bereday, and a contemporary theorist of interreligious learning, J.A. Berling, I will first set up a heuristic apparatus to analyze the process of comparative learning; and then, in the four subsections that immediately follow, I will gradually expose the different, interconnected epistemic procedures of comparative theologians, especially, those of Francis X. Clooney.